PHOTOREDUCTION OF CO2 INTO FORMIC ACID WITHIN AQUEOUS SOLUTION - Auliardi, Dzaky
The increase in the accumulation of CO2 gas, as the main greenhouse gas (GHG), in the earth's atmosphere has caused environmental problems and serious consequences on climate change, so it needs to be addressed. By using the photoreduction principle, carbon dioxide can be converted into high value chemical compounds, one of them is formic acid which can act as a hydrogen carrier. The process of photoreduction efficiency can be increase by using a photocatalyst that can operate in two different photosystems, with a sensitivity range on a different spectrum. The purpose of this study was to determine the effect of the photocatalyst manufacturing operating conditions on the activity of the resulting photocatalyst and to obtain the photocatalyst that had the best performance for the production formic acid. In this study, a photocatalyst based on Layered Double Hydoxide made of zinc, chromium and copper was analyzed by means of coprecipitation and ion exchange methods for CO2 photoreduction in the aquatic phase under visible light irradiation which could produce a formic acid product with high photocatalytic efficiency. The highest yield of formic acid was obtained at a reaction temperature of 100? using a photocatalyst 0.3Cu@Zn-Cr LDH was 21,62 ?mol.grkatalis -1.hr-1. This photocatalyst shows increased activity when the reaction temperature is increased to 60? and 100?. On the other hand, the photocatalyst 0.3Cu2O@Zn-Cr LDH its activity decreased when the reaction temperature was increased to thesame range. This difference occurs because of the self-oxidation mechanism of Cu and Cu2O; on 0.3Cu@Zn-Cr LDH, the oxidation result is Cu2O which still has photocatalytic activity although it eventuallyforms CuO, while at 0.3Cu2O@Zn-Cr LDH, the oxidation result is inactive CuO.